2019
DOI: 10.1159/000503711
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Acne Vulgaris among Adolescents in Kuwait

Abstract: Objectives: The prevalence of acne vulgaris (AV) among adolescents in Kuwait has remained mostly unknown. This study aimed to estimate the prevalence of AV and its predictors among adolescents in Kuwait. Subjects and Methods: A cross-sectional study was conducted on 714 participants who were randomly selected from public schools using multistage cluster random sampling. The presence or absence of AV, as well as severity of AV, were assessed using the Global Acne Grading Scale. Data on risk factors and potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 25 publications
2
8
1
1
Order By: Relevance
“…enrolled Saudi male adolescents to determine the aggravating dietary factors on acne and its prevalence, reporting an increased acne prevalence in adolescents after an excess intake of fat meals, chocolate, spicy food, and soft (cola) drinks 41 . Alkhabbaz et al ., in a study on Kuwait and non‐Kuwait adolescents, found an association between acne prevalence and dietary habits with regard to consumption in the previous 3 months of fruit, fried food, or low‐fat milk 42 …”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…enrolled Saudi male adolescents to determine the aggravating dietary factors on acne and its prevalence, reporting an increased acne prevalence in adolescents after an excess intake of fat meals, chocolate, spicy food, and soft (cola) drinks 41 . Alkhabbaz et al ., in a study on Kuwait and non‐Kuwait adolescents, found an association between acne prevalence and dietary habits with regard to consumption in the previous 3 months of fruit, fried food, or low‐fat milk 42 …”
Section: Resultsmentioning
confidence: 96%
“…Of the 22 cross-sectional studies,17 evaluated the link between acne and dietary pattern, [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] four dealt with acne and dairy products, [49][50][51][52] and one exclusively with the effects of daily intake of sugar from soft drinks 53 (Table 3).…”
Section: Case-control Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…9 The adolescent population is reported to be the most affected as found in a recent study that showed 44.8% (self-reported) and 67.1% (clinical) prevalence of AV among adolescents in Kuwait. 10 A common consequence of acne vulgaris, especially in dark-skinned individuals, is postinflammatory hyperpigmentation (PIH). 11 Similarly, an estimated 95% of AV patients have been reported to have some degree of postacne scarring.…”
Section: Epidemiology Etiology and Pathophysiologymentioning
confidence: 99%
“…One of the commonest skin disorders globally is AV, with an estimated prevalence of 9.4% 9 . The adolescent population is reported to be the most affected as found in a recent study that showed 44.8% (self‐reported) and 67.1% (clinical) prevalence of AV among adolescents in Kuwait 10 . A common consequence of acne vulgaris, especially in dark‐skinned individuals, is postinflammatory hyperpigmentation (PIH) 11 .…”
Section: Introductionmentioning
confidence: 99%